2022
DOI: 10.3390/ijms231810406
|View full text |Cite
|
Sign up to set email alerts
|

Could Alcohol Abuse and Dependence on Junk Foods Inducing Obesity and/or Illicit Drug Use Represent Danger to Liver in Young People with Altered Psychological/Relational Spheres or Emotional Problems?

Abstract: Recent data show that young people, mainly due to the pressure of some risk factors or due to disrupted interpersonal relationships, utilise greater reward value and display greater sensitivity to the reinforcing properties of “pleasurable stimuli”, specifically in those situations in which an enhanced dopamine release is present. Alcoholic beverages, foods rich in sugar and fat, and illicit drug use are pleasurable feelings associated with rewards. Research shows that there is a link between substance abuse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 160 publications
0
11
0
Order By: Relevance
“…Third, despite widespread adjustment in our study, unmeasured confounders such as alcohol consumption may explain part of this association. Alcohol consumption is a great risk factor for liver damage and it's estimated that about 35% of alcohol drinkers developed early liver disease; the issue that might affected by the individual gut microbiome 56,57 . According to the systematic review and meta‐analysis study, 58 one out of eight general population of Iran reported consumption of alcohol despite its legal prohibition.…”
Section: Discussionmentioning
confidence: 99%
“…Third, despite widespread adjustment in our study, unmeasured confounders such as alcohol consumption may explain part of this association. Alcohol consumption is a great risk factor for liver damage and it's estimated that about 35% of alcohol drinkers developed early liver disease; the issue that might affected by the individual gut microbiome 56,57 . According to the systematic review and meta‐analysis study, 58 one out of eight general population of Iran reported consumption of alcohol despite its legal prohibition.…”
Section: Discussionmentioning
confidence: 99%
“…86,87 Moreover, patients with mood disorders are also more related to consumption of junk foods that can drive obesity and obesity-related disorders (e.g., NAFLD, insulin resistance, cardiovascular disorders, etc.). 88 This pattern closely relates to the psychomotor retardation, anhedonia, and fatigue that are very common findings with depression. 86 Along with dietary habits, this lack of physical activity raises the risk of further metabolic disturbances that may later be predictive of NAFLD.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 92%
“…These alterations in reward pathways are predictive of greater substance use (e.g., alcohol, cocaine, and other illicit substances, etc.) that can lead to liver injury and exacerbation of any existing liver inflammation 88 . Hence, on a personal level, psychiatric ailments increase the propensity of an individual toward the aforementioned behavioral risk factors that have been strongly associated with the development of NAFLD 92 …”
Section: Pathophysiological Nexus Between Nafld and Psychiatric Disor...mentioning
confidence: 99%
“…What’s more, the spatially separated cytosolic ADH/mitochondrial ALDH metabolic system easily causes the diffusion of a toxic intermediate of aldehyde, inducing oxidative stress that causes structural and functional damage of the liver . Moreover, alcohol metabolism is affected and reduced by other types of dependence such as illicit drugs, junk food, and smoking, due to enzymatic interference and their pharmacokinetic interactions with alcohol occurring in the liver, exacerbating the progression of ALI . To address these issues, confined catalytic systems with alcohol metabolic reprogramming capability are highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, alcohol metabolism is affected and reduced by other types of dependence such as illicit drugs, junk food, and smoking, due to enzymatic interference and their pharmacokinetic interactions with alcohol occurring in the liver, exacerbating the progression of ALI. 13 To address these issues, confined catalytic systems with alcohol metabolic reprogramming capability are highly desired.…”
Section: Introductionmentioning
confidence: 99%